A blended learning approach for capacity strengthening to improve the quality of integrated HIV, TB, and malaria services during antenatal and postnatal care in LMICs: a feasibility study - Alice Norah Ladur; Uzochukwu Egere; Marion Ravit; Florence Mgawadere; Christopher Murray; Sarah Ann White; Mohammed Hauwa; Rael Mutai; Lucy Nyaga; Shikuku Duncan; Issak Bashir; Olubunmi Olufunmilola Ayinde; et al. (BMC Medical Education)
Abstract Background The blended learning (BL) approach to training health care professionals is increasingly adopted in many countries because of high costs and disruption to service delivery in the light of severe human resource shortage in low resource settings. The Covid-19 pandemic increased the urgency to identify alternatives to traditional face-to-face (f2f) education approach. A four-day f2f antenatal care (ANC) and postnatal care (PNC) continuous professional development course (CPD) was repackaged into a 3-part BL course; (1) self-directed learning (16 h) (2) facilitated virtual sessions (2.5 h over 3 days) and (3) 2-day f2f sessions. This study assessed the feasibility, change in healthcare providers’ knowledge and costs of the BL package in Nigeria, Tanzania, and Kenya. Methods A mixed methods design was used. A total of 89 healthcare professionals, were purposively selected. Quantitative data was collected through an online questionnaire and skills assessments, analyzed using STATA 12 software. Qualitative data was collected through key informant interviews and focus group discussions, analysed using thematic analysis. Results Majority of participants (86%) accessed the online sessions using a mobile phone from home and health facilities. The median (IQR) time of completing the self-directed component was 16 h, IQR (8, 30). A multi-disciplinary team comprising of 42% nurse-midwives, 28% doctors, 20% clinical officers and 10% other healthcare professionals completed the BL course. Participants liked the BL approach due to its flexibility in learning, highly educative/relevant content, mixing of health worker cadres and CPD points. Aspects that were noted as challenging were related to personal log-in details and network connectivity issues during the self-directed learning and facilitated virtual sessions respectively. Conclusion The blended learning approach to ANC-PNC in-service training was found to be acceptable, feasible and cost less to implement compared to face-to-face training approach in the study settings. The BL training approach was effective in improving the knowledge and skills of healthcare providers who participated in the training.